2018
DOI: 10.1002/anie.201707948
|View full text |Cite
|
Sign up to set email alerts
|

An αv‐RGD Integrin Inhibitor Toolbox: Drug Discovery Insight, Challenges and Opportunities

Abstract: There is a requirement for efficacious and safe medicines to treat diseases with high unmet need. The resurgence in αv-RGD integrin inhibitor drug discovery is poised to contribute to this requirement. However, drug discovery in the αv integrin space is notoriously difficult due to the receptors being structurally very similar as well as the polar zwitterionic nature of the pharmacophore. This Review aims to guide drug discovery research in this field through an αv inhibitor toolbox, consisting of small molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
140
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(155 citation statements)
references
References 211 publications
1
140
0
2
Order By: Relevance
“…An example of potential utility in medicinal chemistry is shown from 4am.H ydrogenation of naphthyridine 4am delivers piperidinopyridine scaffold 5,anarginine mimetic [14] and, specifically,akey pharmacophore within RGD avintegrin drug discovery. [15] Them echanism of the process was rationalized by DFT calculations (Scheme 3). [16] Protonation of the substrate 1 by catalyst 6 leads to LUMO-lowered pyridinium ion pair 7, which also benefits from aC H···O hydrogen bond between the C8-H and another of the phosphate oxygen atoms (H···O: 2.33 ).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…An example of potential utility in medicinal chemistry is shown from 4am.H ydrogenation of naphthyridine 4am delivers piperidinopyridine scaffold 5,anarginine mimetic [14] and, specifically,akey pharmacophore within RGD avintegrin drug discovery. [15] Them echanism of the process was rationalized by DFT calculations (Scheme 3). [16] Protonation of the substrate 1 by catalyst 6 leads to LUMO-lowered pyridinium ion pair 7, which also benefits from aC H···O hydrogen bond between the C8-H and another of the phosphate oxygen atoms (H···O: 2.33 ).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…There are currently few antiviral molecules that are effective against SARS-CoV-2 Agents that block integrin binding may provide a promising avenue of research. Known blockers of integrin binding include the antibody natalizumab (a α4β1/β7 integrin antagonist) for the treatment of multiple sclerosis/Crohn's disease, the small molecule tirofiban (an αIIbβ3 inhibitor) for the treatment of acute coronary syndrome, as well as inhibitors of αV RGD-binding integrin (Hatley et al, 2018). Anti-integrin pharmacotherapy is certainly possible, although no treatment is yet available that prevents virus-integrin binding, suggesting that further research is necessary to neutralize these pathogens.…”
mentioning
confidence: 99%
“…Cilengitide inhibits both α v β 3 and α v β 5 , resulting in decreased cell adhesion and migration, and has progressed to late‐stage clinical trials for cancer indications. However, the results of a Phase III study in glioblastoma did not meet their primary endpoint and Cilengitide currently remains unmarketed …”
Section: Introductionmentioning
confidence: 99%
“…However,t he results of aP hase III study in glioblastoma did not meet their primary endpoint and Cilengitide currently remains unmarketed. [6] In general, ligand binding occurs within ac revice at the interface between the a and b integrin subunits, and it is assisted by three metal ions located at the b 3 interface;t he guanidinium side chain of the RGD motif bridges the a chain through an electrostatic clamp with the aspartic acids of the b-propeller domain (a v ), whereas the Asp carboxyo xygen atoms coordi- [ nate the Mn 2 + ion at the metal-ion-dependent adhesion site (MIDAS, bA) and form hydrogen bonds with the b1-a1l oop of the b 3 subunit. Interestingly,e xperimental evidenceh as shown that some RGD-based cyclopeptides, including Cilengitide, do not behavea sp ure antagonists, but rather as partial agonists.…”
Section: Introductionmentioning
confidence: 99%